2020
DOI: 10.17159/wsa/2020.v46.i2.8234
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moistube and subsurface drip irrigation on cowpea (Vigna unguiculata (l.) Walp) production in South Africa

Abstract: Moistube irrigation (MTI) is a new subsurface irrigation technology where the water emits from a semi-permeable membrane at a slow rate depending on applied pressure and soil water potential. There is lack of information on how various crops respond to MTI. This study determined growth, yield and water use efficiency (WUE) of cowpea (Vigna unguiculata (L.) Walp) under varying water regimes under MTI and subsurface drip irrigation (SDI), using field and glasshouse experiments in summer and winter of 2018, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…The use of large amounts of water led to an increase in the length of the head and similarly when little water was used the lowest head length was observed. This can also be due to the adequate dissolution of nutrients at high water levels [8][9][10] mentioned the effect of irrigation treatments on the head length of lettuce at the level of irrigation of 100% ETc which gave the highest average compared to the lowest levels of irrigation.…”
Section: Head Length (Cm)mentioning
confidence: 99%
“…The use of large amounts of water led to an increase in the length of the head and similarly when little water was used the lowest head length was observed. This can also be due to the adequate dissolution of nutrients at high water levels [8][9][10] mentioned the effect of irrigation treatments on the head length of lettuce at the level of irrigation of 100% ETc which gave the highest average compared to the lowest levels of irrigation.…”
Section: Head Length (Cm)mentioning
confidence: 99%
“…Cowpea was planted on 14 February 2018 and deficit irrigation treatments were introduced 21 DAP; other agronomic management practices were done accordingly based on recommended best practices (DAFF, 2014). The description of the experimental design used in this study is found in Kanda et al (2020).…”
Section: Description Of Study Sites and Experimental Designsmentioning
confidence: 99%
“…The water application was applied intermittently, ranging from as low as 3 days, 5 days, and 8 days continuously per 10 days for 100% ETc, 70% ETc and 40% ETc, respectively. The description of the irrigation management is found in Kanda et al (2020).…”
Section: Irrigation Management and Actual Evapotranspirationmentioning
confidence: 99%
See 2 more Smart Citations